Insights into the Role of the Berry-Specific Ethylene Responsive Factor VviERF045 - Leida, Carmen; Dal Rì, Antonio; Dalla Costa, Lorenza; Gómez, Maria D.; Pompili, Valerio; Sonego, Paolo; Engelen, Kristof; Masuero, Domenico; Ríos, Gabino; Moser, Claudio (Frontiers in Plant Science, 2016)
During grape ripening, numerous transcriptional and metabolic changes are required in order to obtain colored, sweet, and flavored berries. There is evidence that ethylene, together with other signals, plays an important role in triggering the onset of ripening. Here, we report the functional characterization of a berry-specific Ethylene Responsive Factor (ERF), VviERF045, which is induced just before véraison and peaks at ripening. Phylogenetic analysis revealed it is close to the SHINE clade of ERFs, factors involved in the regulation of wax biosynthesis and cuticle morphology. Transgenic grapevines lines overexpressing VviERF045 were obtained, in vitro propagated, phenotypically characterized, and analyzed for the content of specific classes of metabolites. The effect of VviERF045 was correlated with the level of transgene expression, with high-expressing lines showing stunted growth, discolored and smaller leaves, and a lower level of chlorophylls and carotenoids. One line with intermediate expression, L15, was characterized at the transcriptomic level and showed 573 differentially expressed genes compared to wild type plants. Microscopy and gene expression analyses point towards a major role of VviERF045 in epidermis patterning by acting on waxes and cuticle. They also indicate that VviERF045 affects phenolic secondary metabolism and induces a reaction resembling a plant immune response with modulation of receptor like-kinases and pathogen related genes. These results suggest also a possible role of this transcription factor in berry ripening, likely related to changes in epidermis and cuticle of the berry, cell expansion, a decrease in photosynthetic capacity, and the activation of several defense related genes as well as from the phenylpropanoid metabolism. All these processes occur in the berry during ripening.